Comparative Analysis of Glandular and Extraglandular Manifestations in Primary and Secondary Sjögren’s Syndrome: A Study in Two Academic Centers in North-East Romania - Alexandru Lodba; Codrina Ancuta; Diana Tatarciuc; Angela Ghiorghe; Luciana-Oana Lodba; Cristina Iordache (Diagnostics, 2024)
Background: This study investigates the clinical characteristics and differences between primary Sjögren’s Syndrome (pSS) and secondary Sjögren’s Syndrome (sSS) in a cohort of 50 patients. Methods: Conducted across two academic facilities in North-East Romania, the study emphasizes the importance of glandular and extraglandular manifestations, focusing on salivary flow rates, pH levels, and buffer capacity. Patients were diagnosed using the 2016 ACR-EULAR classification criteria, with a detailed examination including salivary tests, biopsies, and antibody presence. Results: The findings highlight significant differences between pSS and sSS, particularly in salivary function, with pSS patients exhibiting more severe glandular dysfunction. The study also notes a higher prevalence of inflammatory joint involvement in sSS patients, often associated with rheumatoid arthritis. Statistical analysis revealed correlations between salivary parameters and disease progression, underscoring the necessity of tailored treatment strategies. The research suggests that lower salivary flow rates and altered pH levels in pSS patients contribute to compromised oral health, including increased dental cavities and periodontal disease. Conclusions: The study’s results contribute to a deeper understanding of Sjögren’s Syndrome and reinforce the need for multidisciplinary management to address both systemic and oral health complications in these patients.